Iceland’s “Egg of Life” and the Modern Media - Kristmannsson, Gauti (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractThis paper provides an overview of Icelandic language politics in the face of the challenges brought on by the modern media in a small country. It starts with a short glance at the beginnings of Icelandic linguistic politics in the nineteenth century to reveal the basic ideological premises and show how they have been maintained in national discourse on the Icelandic language and the media. It then examines how the Icelandic national consensus on linguistic purism has been shaken by technological and political developments, in short the advancing globalisation of the media. These developments are reflected in the practices of media translation and changing attitudes towards translation.